The global burden of illness of peanut allergy: A comprehensive literature review. Issue 5 (16th January 2021) - Lieberman, Jay A.; Gupta, Ruchi S; Knibb, Rebecca C.; Haselkorn, Tmirah; Tilles, Stephen; Mack, Douglas P.; Pouessel, Guillaume
Abstract: Peanut allergy (PA) currently affects approximately 2% of the general population of Western nations and may be increasing in prevalence. Patients with PA and their families/caregivers bear a considerable burden of self‐management to avoid accidental peanut exposure and to administer emergency medication (adrenaline) if needed. Compared with other food allergies, PA is associated with higher rates of accidental exposure, severe reactions and potentially fatal anaphylaxis. Approximately 7%–14% of patients with PA experience accidental peanut exposure annually, and one‐third to one‐half may experience anaphylaxis, although fatalities are rare. These risks impose considerably high healthcare utilization and economic costs for patients with PA and restrictions on daily activities. Measures to accommodate patients with PA are often inadequate, with inconsistent standards for food labelling and inadequate safety policies in public establishments such as restaurants and schools. Children with PA are often bullied, resulting in sadness, humiliation and anxiety. These factors cumulatively contribute to significantly reduced health‐related quality of life for patients with PA and families/caregivers. Such factors also provide essential context for risk/benefit assessments of new PA therapies. This narrative review comprehensively assessed the various factors comprising the burden of PA.